1997
DOI: 10.1046/j.1471-4159.1997.69041771.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Monoamine Oxidase Contributes to the Protective Effect of 7‐Nitroindazole Against MPTP Neurotoxicity

Abstract: The ability of 7‐nitroindazole (7‐NI) to protect against MPTP‐induced neurotoxicity has been attributed to its inhibition of neuronal nitric oxide synthase. In the present study, 7‐NI was found to counteract almost completely striatal dopamine depletion caused by a single subcutaneus injection of 20 mg/kg MPTP in mice. This effect, however, was accompanied by a significant reduction in the striatal levels of MPP+, the toxic metabolite generated via monoamine oxidase B‐catalyzed MPTP oxidation. In the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…Besides inhibiting nNOS, 7-NI is also a good inhibitor of MAO-B, and indeed Di Monte and coworkers have attributed to this mechanism the neuroprotective effect of 7-NI against MPTP in mice (Di Monte et al, 1997). However, the mechanism of action of 6-OHDA differs from that of MPTP, and so inhibition of MAO-B is unlikely to affect 6-OHDA toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Besides inhibiting nNOS, 7-NI is also a good inhibitor of MAO-B, and indeed Di Monte and coworkers have attributed to this mechanism the neuroprotective effect of 7-NI against MPTP in mice (Di Monte et al, 1997). However, the mechanism of action of 6-OHDA differs from that of MPTP, and so inhibition of MAO-B is unlikely to affect 6-OHDA toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, peroxynitrite can decompose to form •OH and nitrogen dioxide radicals (26), thereby initiating lipid peroxidation and DNA oxidation, phenomena well documented in nigral tissue from PD patients (27)(28)(29). Interestingly, the role of NO• in MPTP-induced toxicity has been challenged recently because 7-nitroindazole, a NOS inhibitor, may also act as a MAO inhibitor or as an atypical antioxidant (30)(31)(32).…”
Section: Sod1mentioning
confidence: 99%
“…Di Monte et al (1997) found that the protective effect of 7-NINA against (MPTP) neurotoxicity was not due solely to nNOS inhibition.…”
Section: Effects Of 7-nina On K + -Evoked Csd Initiationmentioning
confidence: 99%